2c-3=12(6-c)+7c

Simple and best practice solution for 2c-3=12(6-c)+7c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c-3=12(6-c)+7c equation:



2c-3=12(6-c)+7c
We move all terms to the left:
2c-3-(12(6-c)+7c)=0
We add all the numbers together, and all the variables
2c-(12(-1c+6)+7c)-3=0
We calculate terms in parentheses: -(12(-1c+6)+7c), so:
12(-1c+6)+7c
We add all the numbers together, and all the variables
7c+12(-1c+6)
We multiply parentheses
7c-12c+72
We add all the numbers together, and all the variables
-5c+72
Back to the equation:
-(-5c+72)
We get rid of parentheses
2c+5c-72-3=0
We add all the numbers together, and all the variables
7c-75=0
We move all terms containing c to the left, all other terms to the right
7c=75
c=75/7
c=10+5/7

See similar equations:

| X⁴-9x³=0 | | {e}{5}-14=8 | | 9-3x+x=5 | | {c}{9}+16=17 | | X-5=9x | | 3b–7=5 | | (2x+5)(x−4)=0 | | 1+–2u=–7 | | 13(x-9)=23(x-7) | | x(x-0,5)(x-1)=0 | | x÷6-11=-8 | | 1+–2t=–1 | | 4x+x=480 | | 3−–2u=1 | | -v+-6=-9 | | u2–26u=0 | | 2x+30=5x+15 | | 1+7n-3n=-9+3n+6+5 | | 6x+3(x-4)=5(x+4) | | 5x+3/6=3 | | 5y-3(3+1)=2y+6(3)+6 | | 7x+8=-5x+32 | | 7x+35=–105 | | 3(h-6)=5(2h+2) | | 5x■=35 | | r4-8=5 | | 15+6v=9v | | 2x+3=-4x+2 | | -2=3(2y-4) | | 10x–7+2x=41 | | 14=-4+6x | | —3x-2x=3(—10) |

Equations solver categories